Enhancement of flushed sediment in pressure flushing using inclined plates upstream of orifice - Nima Najafi; Mehdi Daryaee; Seyed Mahmood Kashefipour (Water Supply, 2022)
Pressure flushing is a common technique to restore the storage capacity of reservoirs. However, the low quantity of flushed sediment remains a drawback of pressure flushing. Experimentally, the present study used inclined plates upstream of the bottom outlet to increase the flushed sediment in pressure flushing. The variables included the plate width (B), the angel between the vertical line at the outlet center and the normal vector of the inclined plate (α), radial distance of the inclined plates from the orifice center (R), and outlet discharge (Q). The results showed that the flushed sediment significantly enhanced; the quantity of flushed sediment for B = 6.3 cm, α = 60°, R = 8.5 cm, and a Q = 8.34 L/s was 19 times as large as that in the reference test (i.e., without plates). Furthermore, the length, width, and depth of the scour cone in the presence of inclined plates were 3, 2.3, and 3.3 times as high as those in the absence of the inclined plates. Also, equations were developed to predict the volume and dimensions of the scour cone in the presence of inclined plates based on the experimental data. Finally, the importance of the variables was determined using a sensitivity analysis method. Between all considered parameters in this study, the plate distance from the outlet was found to have the highest effect and the plate inclination the lowest effect (three times) in increasing the flushed sediment through the orifice. HIGHLIGHTS Increasing pressure flushing efficiency.; Reducing discharged water volume during pressure flushing operation.; Prevention of sediment deposition close to bottom outlet.;